Legend Categories and Structure in Nagari Sungai Limau Dharmasraya District and Its Implications for Indonesian Language Learning - Fauzi, Ahmad; Nurizzati, Nurizzati (JOLLT Journal of Languages and Language Teaching, 2024)
Folklore as a source of cultural information for a community group needs to be studied, which then needs to be introduced and socialized to other community groups. Legends have the potential and role as cultural treasures. Legends also have educational value that can be appreciated, pondered and appreciated. This research aims to describe the categories and structure of legends in Nagari Sungai Limau, Dharmasraya Regency and the implications for learning. This type of research is qualitative using descriptive methods. The source of research data is a legend in Nagari Sungai Limau, Dharmasraya Regency. Research data collection techniques use observation, data, interviews and data techniques. Data analysis techniques are carried out by classifying or grouping data, analyzing categories and legend structures, drawing conclusions from the entire research work process, and compiling and reporting research results. The results of the research are: first, there are two categories of legends, namely local legends consisting of the Lubuk Tagadih legend and Lubuk Tosau legend and supernatural world legends consisting of Wang Binun (Binun People) and the Plisit legend. Second, the structure of legends in Nagari Sungai Limau, Dharmasraya Regency generally contains theme, plot, characters, setting and message. Third, the implication in learning is in the Basic Competency that it examines the structure and language of local fables/legends that are read and listened to. Therefore, the current study can be concluded that a category includes local legends and supernatural legends, the structure of the legend which includes theme, plot, characters, setting, and message.